Aku Ingin Seperti Pitung Pada Cerita Bergambar - chaerani, bunga (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2023)
Picture stories can increase children's interest in reading from an early age so that children's brains are stimulated to develop, have higher imagination power, and increase vocabulary in children's speech by providing reading books that attract children's interest according to their age with stories containing various information about life experiences to develop their fantasy power. This research uses qualitative methods with a research type approach that is research-led practice. Where to carry out research in the field first and then apply it in practice to the process of creating Fine Art works in the form of printed illustrated stories. The artist's work in the form of a book entitled "The Journey of a Champion from Betawi Episode 1: Swapped Roles" was changed to, the printed illustrated story was made into 3 (three) works with different stories but with the same title, namely "I Want to be Like Pitung". Create work 1 that says Episode 1: Ali Likes to Protect, for work 2 that says Episode 2: Ali Likes to Help, and for work 3 that says Episode 3: Ali Likes to Share.